Wolność w nauczaniu św. Pawła na tle kultury judaistyczno-hellenistycznej - Jan Klinkowski (Wrocławski Przegląd Teologiczny)
Totalitarian systems of the 20th century questioned human freedom. Freedom, almost absolute, was then usurped by dictators manipulating with social structures. Liberal society became an alternative then, and the rights of a individual, realised in open economic space became fundamental. As a result, societies of consumers emerged and they questioned a lot of basic moral rules, in the name of human freedom. Paradoxically, in societies which referred to ideals of freedom, arose many fields where human freedom was captivated. Christians, in their search for solutions to everyday life problems, referred to biblical texts. St. Paul was a teacher of the lifestyle that was liberating from the bonds of the Law. His appearances referred to the teaching of Jesus, who proclaimed the time for freedom in his inaugurating speech in the Nazareth synagogue (Lk, 4,16-30). Paul, following Jesus’ teaching, noticed that the Law, more and more detailed in the Pharisaic interpretation, was beginning to subjugate people. Christians were invited to live in freedom based on the foundation of love between God and Man. However, St. Paul’s teaching was wrongly interpreted within the Corinthian community, leading to moral liberty which consequently could have been the origin of new bonds. Therefore Paul had to define the limits of human freedom so as it did not lead to the degradation of social relations as well as from individual people. In the background of his reflection there is the Old Testament tradition of presenting the human as the one that was created in the image of God, hence the idea of the filiation of God. A child loving its Father wants to fulfill his will. Paul was aware that the recipients of his teaching would also be people who had been brought up in a Hellenic culture, that is why he referred to the ideals of virtues formed in the pluralistic society of the Roman Empire. All people, regardless of their cultural heritage, need liberation from the bonds of sin and death. Thus Paul in his Epistle to Romans presents a new dimension of Jom Kippur which, thanks to the sacrifice of Jesus Christ, is celebrated in order to purify not only Israel but all people who believe in the Crucified and repent of their sins. The sacrifice of Jesus Christ opens the way to liberation from the sins and to full freedom, which can be achieved by „God’s child” at „the Father’s home”.